Digital storytelling learning application for Malaysia history on 'Kedah Tua' kingdom using constructivism approach - Tee, Siew Xuan (2022)

(untitled)
This project is about a Digital Storytelling Learning Application for Malaysia History on 'Kedah Tua' Kingdom using Constructivism Approach. History is one of the most important academic pursuits of any child’s education and a valuable academic subject for people to learn. Therefore, digital storytelling learning application may retain history and continue in the future compared to the traditional learning history method. Since the beginning of the Great Recession in 2007, the history major has lost significant market share in academia. The reasons why people don’t want to learn history is because they find it boring and the current history application in the market is not interactive and the content that provide user is not attractive because lack of multimedia technology. Hence, this digital storytelling learning application is to design and develop an interactive media-rich e-storytelling learning application for secondary school education. That means it will provide people to learn history digitally and make it more interesting when learning history. The digital storytelling learning application will connect with the power of interactive multimedia. Thus, the project will implement Augmented Reality (AR) and 3-Dimensional (3D) modeling views of the ancient building and archeological side views of the building. In addition, the project also will illustrate the 2D view of the history. This project will follow ADDIE model as the methodology for the software development. So that users can enjoy a better and more interesting way of learning history. Furthermore, this study is looking at how digital storytelling learning application simplifies the learning experience and enhance the student experience of the digital storytelling learning application.